2016
DOI: 10.1111/jre.12377
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor‐1α inhibits interleukin‐6 and ‐8 production in gingival epithelial cells during hypoxia

Abstract: inducible factor-1a inhibits interleukin-6 and -8 production in gingival epithelial cells during hypoxia.Background and Objective: Hypoxia has been widely studied in inflammatory diseases as it can modulate the inflammatory response, mainly via the hypoxiainducible factor (HIF). However, little is known about the effects of hypoxia and the role of HIF in the inflammatory responses to periodontitis. In this study, we focused on the gingival epithelium that is exposed to relatively low levels of oxygen. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…According to a previous study (Takedachi et al 2017), in our post mortem samples, HIF-1a immunostaining was higher in the oral epithelium than it was in the sub-oral connective tissues, thus reflecting the in vivo distribution observed in mice under hypoxic-inflammatory conditions. Interestingly, as shown in the epithelial cells in a rat model, in which the level of HIF-1a expression was relatively higher in the suprabasal layer, our results indicated a high staining reactivity for HIF-1a that was detectable in the deeper layers of the oral mucosa and decreased gradually in the more superficial layers.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…According to a previous study (Takedachi et al 2017), in our post mortem samples, HIF-1a immunostaining was higher in the oral epithelium than it was in the sub-oral connective tissues, thus reflecting the in vivo distribution observed in mice under hypoxic-inflammatory conditions. Interestingly, as shown in the epithelial cells in a rat model, in which the level of HIF-1a expression was relatively higher in the suprabasal layer, our results indicated a high staining reactivity for HIF-1a that was detectable in the deeper layers of the oral mucosa and decreased gradually in the more superficial layers.…”
Section: Discussionsupporting
confidence: 79%
“…Hydroxylation by the prolyl-4-hydroxylases (PHDs) or HIF-1 prolyl hydroxylases of one of two critical proline residues in their oxygen-dependent degradation domain mediates their interaction with the von Hippel-Lindau (VHL) E3 ubiquitin ligase complex that targets them for rapid proteasomal degradation (Bruick & McKnight, 2001;Hirsil€ a et al 2005;Ng et al 2011;Masoud & Lin, 2015). Because the hydroxylation action from PHDs requires the presence of oxygen, a hypoxic environment will inhibit the activities of the HIF-P4Hs such that HIF-1a escapes degradation, translocates to the nucleus and binds HIF-b; this dimer then recognizes the HIF-responsive elements in a number of hypoxia-inducible target genes (Bruick & McKnight, 2001;Hirsil€ a et al 2005;Masoud & Lin, 2015;Vasconcelos et al 2016;Takedachi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In response to the hypoxic condition induced by the inflammatory disease, activation of HIF-1-α is increased and mechanisms that correct the hypoxic state are developed 3 . Researches evaluating HIF-1-α levels in healthy and inflamed periodontal tissues have reported that HIF-1-α levels were higher in inflamed periodontal tissues 6 , 36 , 37 It has been reported that hypoxic responses of HIF-1-α in periodontal tissues may produce negative feedback mechanisms in the inflammation 6 . These finding demonstrate the importance of the level of HIF-1-α in infectious periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor −1 alpha (HIF-1-α) is one of the HIF-alfa subunits that are the main sensors of hypoxia 5 . HIF-1-α is the main regulatory protein that provides adaptation to hypoxic conditions 6 . HIF-1-α has been shown to be activated by proinflammatory signals in periodontal cells 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism suggested for the progression of periodontal destruction with excessive occlusal forces is that tooth mobility creates a subgingival environment conducive to overgrowth by periodontal pathogens (8). A possible association with occlusal trauma, microbiota and periodontal inflammation might be hypoxia due to periodontal pathogens such as Porphyromonas gingivalis and Fusobacterium nucleatum (9,10). Furthermore, apart from periodontal infection, hypoxia can lead to inflammation with up-regulating pro-inflammatory mediators such as receptor activator of nuclear factor-kB ligand (RANKL) and interleukin (IL)-1β (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%